(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In the present article it will be analysed and associated the concepts of nature, body and potency based on Spinoza and Marx, from this point it will be suggest that the act of man’ exteriorization (and his essence) it’s not only social, but also productive in the sense of praxis and activity of itself and of social. In this sense, this creative act is based in the contemporary world in the daily experience of inhabit the city, the one, under capitalism, is been reduced to an habitat’aesthetic, by process of material and subjective domination which pretend the social practices’ standardization, separating man’s potency, inverting the affective order and, by conclusion, separating corporality and the cognitive sphere of men.